Influence of temperature and compressive stress on the UMo/Zry-4 interdiffusion layer. (January 2017) - López, Marisol; Picchetti, Bianca; Taboada, Horacio
Abstract: The miniplates fabrication process involves the co-rolling at high temperatures of a welded ensemble made up of a monolithic Uranium-Molybdenum (UMo) core surrounded by a frame and two Zircalloy-4 (Zry-4) covers. The alloys employed in this work contained 10% (mass) of Molybdenum (Mo). Temperature and compressive stress are both important parameters in the co-rolling process, since they can modify the interaction between components. Not only is a thicker interlayer obtained when working at 800 °C, but also regions rich in Molybdenum. A thin interlayer appeared at 650 °C, deep enough to correctly bond both materials. However, no regions rich in Molybdenum are observed in these conditions. When working with a high compressive stress, the results were similar to those obtained at 800 °C. Compared to the co-rolling process, the interlayer obtained in diffusion couple samples (prepared by attaching the materials by means of a press) is not visible. Furthermore, a longer contact time –between UMo and Zry-4- and higher temperatures are necessary. This paper presents the experimental results achieved with diffusion couples in several conditions, in addition to a comparison with the observations of the miniplates fabrication process. Highlights: High co-rolling temperatures results in regions rich in molybdenum. Working at high compressive stress has the same effects as working at 800 °C. The optimum conditions for the co-rolling process are a low compressive stress and a temperature of 650 °C.